Analysis of Internet Network Quality of Service (QoS) on ULM Hotspot at Universitas Lambung Mangkurat Banjarmasin - Rizky Fatra Wijaya (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2024)
With the internet, the technique of having information or records will become quicker and extra efficient. present day college students are very dependent on the internet in phrases of gaining knowledge of, doing assignments, accumulating assignments, even within the studying method using the internet. the present facility at Lambung Mangkurat university is ULM HOTSPOT to facilitate college students to get entry to the internet without cost, however at certain times ULM HOTSPOT regularly decreases its network speed. The intention of the research became to analyze the quality of the ULM HOTSPOT network in five faculties of Lambung Mangkurat university, Banjarmasin, specifically the faculty of Engineering ULM, faculty of Eco- nomics and business ULM (FEB ULM), faculty of teacher training and education ULM (FKIP ULM), faculty of Social and Political Sciences ULM (FISIP ULM), in addition to the ULM faculty of law, by using searching out parameter calculations for quality of provider, particularly Throughput, Jitter, delay, and Packet Loss primarily based on TIHPON standardization and in order to be able to discover what factors impact the parameter values of quality of service. The research turned into accomplished by collecting parameter data from quality of service using the network Protocol Analyzer software, specifically Wireshark in five faculties of Lambung Mangkurat university, Banjarmasin through getting access to the ULM HOTSPOT network in each faculty and establishing Simari, Gmeet, and Zoom as substances for accumulating quality of service parameter records. . The outcomes of this observe obtained a quality of service rating based on standards from TIHPON, faculty of Engineering with a rating of 2.75 (Unsatisfactory), FEB-ULM with a rating of 3 (excellent), FKIP-ULM with a value of 2.75 (Unsatisfactory), FISIP-ULM with a value of 3 (excellent), and the faculty of law with a value of 3 (excellent). The factors that have an effect on the decrease within the quality of service rating based on the ULM HOTSPOT internet network consumer capability exceeds the limit.